Evaluation of Digital Business Model Opportunities : A Framework for Avoiding Digitalization Traps - Linde, Lina; Sjödin, David; Parida, Vinit; Gebauer, Heiko (Routledge, 2021)
In the era of digitalization, manufacturing firms find it difficult to assess what is “the right” digital business model. To avoid common digitalization traps, company leaders and managers need to carefully assess each business model opportunity before committing to implementation and commercialization. We present insights from our case study about the diverse and complex issues related to digital business models. We highlight three digitalization traps and provide a three-phase framework companies can use to evaluate digital business model opportunities and make an informed decision on the commercial prospects for each model vetted.
Keywords: Business model innovation; Digitalization paradox; Digital servitization; industry 4.0; Risk management; fi=Strateginen johtaminen|en=Strategic Management|